An updated incidence of paediatric achalasia and number of myotomies performed in the United Kingdom. Issue 7 (24th September 2021) - Dokal, Kitt; Mutalib, Mohamed
Summary: Background: Achalasia is a rare condition characterised by an absent oesophageal peristalsis and a non‐relaxing lower oesophageal sphincter. The incidence of paediatric achalasia is poorly studied and inconsistently reported. We aimed to provide an up to date incidence of paediatric achalasia in the UK. Methods: All United Kingdom hospitals with paediatric gastroenterology and/or paediatric surgery were contacted to provide data on achalasia diagnosis and myotomies performed (2008‐2020). Hospital Episode Statistics includes diagnostic and procedural data for all hospitals in England that were searched for achalasia and myotomy in children (1998‐2020). Proxy data (epilepsy diagnosis) were used to compare diagnosis. Results: The incidence of paediatric achalasia in the UK was 0.38 (England 0.43, Wales 0.09, Scotland 0.15 and Northern Ireland 0.17) per 100 000 population per year. The number of myotomies performed remained stable with an average of (±SD) 11.6 (±5) from 2000 to 2020, however, there was a gradual increase in achalasia admissions 58.4 (±19) in the same time period. Using epilepsy as proxy condition, hospitals appear to diagnose achalasia predominantly from their geographic catchment population raising concerns about underdiagnosing achalasia in children. Conclusion: The incidence of paediatric achalasia in the UK is significantly higher than previously reported. Although this is still lower than the incidence in adults, the gap is narrowing. There is evidence to suggest an ongoing underdiagnosis of achalasia in childhood contributing to the wide variation in care across the UK.